COMPARATIVE CHARACTERISTICS OF THE NEUROLOGICAL STATUS OF INFANTS BORN IN THE I AND II PHYSIOLOGICAL POSITIONS - E. A. Morozova; A. V. Petrova; A. A. Khasanov (Русский журнал детской неврологии, 2016)
Objective: to provide the comparative characteristics of neurological impairments in infants born in the I and II obstetric positions and to follow them up in the neonatal period.Subjects and methods. A total of 133 infants born by vaginal delivery at 38–41 weeks» gestation in 2014 to 2016 were followed up. All the examinees were divided into 2 groups: 1) 71 neonates born in the I obstetric position; 2) 62 babies born in the II position. Their clinical examination encompassed an analysis of the course of delivery, neurological examination of the newborn in the first hours of life with a subsequent follow-up evaluation at the time of his/her discharge from the maternity unit.Results and discussion. The examined groups were comparatively analyzed in terms of a number of indicators. The data of objective neurological examination showed a significant difference in some symptoms: cephalohematoma and torticollis were more common in the group of infants born in the II position. Comparison of the frequency of neurological impairments at different follow-up stages (at birth and at discharge from the maternity unit) revealed their statistically significant reduction in both groups. However, the frequency of neurological symptoms among Group 1 infants (born in the I position) at their discharge from the maternity unit was significantly reduced (from 77.5 to 38.0 %; p < 0.001), and those in Group 2 infants (born in the II position) substantially unchanged (from 87.1 to 79.0 %; p = 0.125). The slight regression of neurological symptoms in Group 2 suggests that intranatal nervous system damage is more severe in the infants born in the II position.Conclusion. To define the position of a fetus during labor is an important component in the prevention of intranatal injuries